Pengaruh Pendekatan Pembelajaran STEM Berbantuan Platform Alef Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Siregar, Mutiara Anjani; Siregar, Tanti Jumaisyaroh (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2024)
Problem-solving ability is one of the primary goals in mathematics education. One approach that can optimize problem-solving skills is the STEM (Science, Technology, Engineering, and Mathematics) approach, supported by the Alef Education platform as a learning medium for mathematics. This study aims to examine the effect of the STEM learning approach assisted by the Alef platform on students' problem-solving skills at the junior high school (MTs) level. The research employs a quantitative method with a quasi-experimental design, specifically the nonequivalent control group design, to enhance students' mathematical problem-solving abilities. The subjects of this study were seventh-grade students of MTs YPRA Batang Kuis. The instrument used to collect data was a mathematical problem-solving skills test. The results of the study indicate that the STEM learning approach assisted by the Alef platform significantly improves students' mathematical problem-solving skills compared to conventional learning methods.